Prevalence Of Yeast and Yeast Like Fungi In Bovine Mastitis And Their In Vitro Drug Sensitivity - Sukumar K (Department of Microbiology, College of Veterinary and Animal Sciences, 1996)
A total of 200 milk samples from clinical cases of bovine mastitis were culturally screened during a period of six months. Pathogenic fungal organisms could be isolated only from 26 samples. Out of this 26 positive samples, yeast and yeast like fungal organisms were isolated from 20 samples and mould from six cases. The major pathogen isolated were candida spp namely C. tropicalis, C. parapsilosis and C. guillermondi. The other organisms were Geotrichum candidum, Trichosporon cutaneum, Sacharomyces cerevisiae, Torulopsis spp and Rhodotorula rubra. The filamentous fungi isolated were Sepedonium spp, Aspergillus ochraceous group, Cladosporium carrionii, Penicillium spp and Trichophyton verrucosum. In majority of the cases yeast and yeast like fungi produced chronic mastitis in which hardness of udder and reduction in milk yield with watery milk containing flakes were noticed. In cases of mastitis where in mould was involved, chronic mastitis characterized by hardness of udder and reduction in milk yield with straw yellow coloured milk, viscid in consistency. Sensitivity pattern of the fungal isolates to the commonly employed antifungal chemotherapeutic agents like Amphotericin B, Clotrimazole, Fluconazole, Griseofuivin, Itraconazole, Ketocanazole, Nystin and Pimaricin (Natamycin) was elucidated. Among the above agents Clotrimazole and Itraconazole exhibited maximum inhibitory activity. All the isolates were found to be resistant to Griseofulvin. In vitro drug sensitivity pattern of fungal isolates employing the discs impregnated with essential oils of cinnamon, clove and lemon grass and alksloids of Cassia alata was studied. Cinnamon leaf oil possessed maximum antifungal activity and the extracts of Cassia alata failed to evince the ability to inhibit the growth of fungal isolates. The antifungal activity of plant extracts were compared with the commonly antifungal chemotherapeutic agents.